Optimal balance: alkali metal-doped boron carbide nanosheets achieve superior stability and nonlinear optical responsiveness - Yaqoob, Junaid; AlMohamadi, Hamad; Khan, Asim Laeeq; Yasin, Muhammad (Royal Society of Chemistry, 2024)
Nonlinear optical (NLO) materials play a vital role in various technological domains, including optoelectronics and photonic devices. Designing NLO materials, particularly inorganic ones, that strike a compromise between nonlinear optical sensitivity and stability has always been a difficult task. In order to improve the stability and NLO responsiveness, we propose and examine alkali metal-doped boron carbide nanosheets (M@BCNs) in this study. Calculated interaction energies (Eint), which span from −65.5 to −94.9 kcal mol−1, show the stability of the M@BCN complexes. The first hyperpolarizability value has also increased, to a maximum of 3.11 × 105 au, indicating improved nonlinear optical characteristics. QTAIM (quantum theory of atoms in molecules) and NCI (non-covalent interactions) analyses demonstrate the validity of the interactions. According to NBO (natural bond orbital) analysis, the alkali metals gain almost +1 charge. Due to the low transition energies and considerable charge transfer between the alkali metals and nanosheet, the nonlinear optical response is significantly improved. The M@BCN complexes also show transparency in the ultraviolet region, with absorption maxima ranging from 917 to 2788 nm. This study proposes a viable approach for developing alkali metal-doped boron carbide nanosheets with improved NLO response and stability.